EXPRESSION OF THE PROGMATIC CONTENT THROUGH CONSONANTS IN IQBOL MIRZA'S POEMS - Hamrakulova Guluzro Dilmurodovna (Scholars Digest Publishing, 2023)
The use of phonetic units in Iqbal Mirza's poems is his poetic skill, creative possibilities of style. Concept of artistic text. The scope of phonopoetic research in the Uzbek language. Types of art based on the melodiousness of sounds. Use of phonetic units in an artistic work and artistic-linguopoetic features.
Keywords: antithesis, phonopoetics, alliteration, assonance, aesthetic effect, aesthetic task, methodological tool.